Easy Tech Enterprise - "Ca Grader" / Mohd Fakrul Faris Zulkaply...[et.al] - Zulkaply, Mohd Fakrul Faris; Alwi, Muhammad Lukman; Che Abah, Nor Hazami; Denan, Nurfidatul; Nording, Muhamad Norhisyam (Faculty of Plantation and Agrotechnology, 2017)
Our company, Easy Tech Enterprise is a company that is more customer oriented business that invented new creation of tools and equipment based on the need from the customer and current problem that they are facing in managing their plantation sector especially in grading the citrus. Based on feasibility study, that have been studied before, we managed to clarify that Jasin is one of the suitable places that have high potential to develop our company. Easy to get supplier and raw material is one of the causes that why we choose Jasin as our first branch, apart from that Jasin is known as one of the develop district in agriculture sector and it near to Muar, Johor and Gemas, Negeri Sembilan which is also develop in agriculture sector. Easy Tech Enterprise are consist of several main pillar that support our company that hold the position for each department respectively but working together as a team in order to achieve and meet the company mission and vision. We provided a best product to use by people and give good benefit to them. One of main our product is CA Grader, where it was produce to ease in grading the citrus and enhances the productivity of smallholder who own citrus farm as well. We can say that our company hope to be one of the companies in Malaysia that may provide and supplies this product to all citrus farmers in Malaysia.